2004
DOI: 10.1093/brain/awh153
|View full text |Cite
|
Sign up to set email alerts
|

Elevated white matter myo-inositol in clinically isolated syndromes suggestive of multiple sclerosis

Abstract: Normal-appearing white matter (NAWM) in established multiple sclerosis has been shown to be abnormal using a variety of magnetic resonance (MR) techniques, including proton MR spectroscopy ((1)H-MRS), although the stage at which these changes first appear is less clear. Using a 1.5 T scanner and single-voxel (1)H-MRS [TR 3000 ms, TE 30 ms, point-resolved spectroscopy (PRESS) localization], we determined NAWM metabolite concentrations in 96 patients a mean of 19 weeks (range 12-28 weeks) after onset of a clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
136
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(160 citation statements)
references
References 59 publications
17
136
6
Order By: Relevance
“…MS converters showed evidence of axonal damage in terms of tNAA decrease compared to healthy controls, while non-converters did not [75]. Regarding prognostic purposes, these results obtained at 3 T are in line with 1.5-T results demonstrating significantly lower tNAA concentration in patients converting to definite MS within 1 year and higher mIns concentration in converters within 3 years time [76].…”
Section: Quantitative Mri Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…MS converters showed evidence of axonal damage in terms of tNAA decrease compared to healthy controls, while non-converters did not [75]. Regarding prognostic purposes, these results obtained at 3 T are in line with 1.5-T results demonstrating significantly lower tNAA concentration in patients converting to definite MS within 1 year and higher mIns concentration in converters within 3 years time [76].…”
Section: Quantitative Mri Methodssupporting
confidence: 84%
“…In patients presenting with CIS, however, significant axonal damage could only be observed in whole brain analysis including normal-appearing brain tissues and lesions but not in the NAWM alone [70]. In contrast, mIns concentrations seem to be increased in the NAWM of CIS patients [71,72]. All these studies dealing with metabolic alterations in MS and CIS patients were performed at field strengths up to 1.5 T.…”
Section: Quantitative Mri Methodsmentioning
confidence: 99%
“…We previously demonstrated, using voxel-based analysis of brain magnetization transfer ratio (MTR) maps, a sensitive technique allowing to evidence subtle tissue injury outside T 2 visible lesions, that in patients with early MS, long range white matter tracts were significantly injured, without diffuse injury in the cortex (Ranjeva et al, 2004). Moreover, MR studies performed in patients at the early stage of the disease have demonstrated that tissue injury was mostly characterized by demyelinating processes, without significant axonal loss Fernando et al, 2004;Ranjeva et al, 2003). Connectivity disturbance may also be responsible for the elevated threshold for access to consciousness evidenced in patients with schizophrenia (Delcul et al, 2006;K.…”
Section: Subliminal Processing and Conscious Access In Multiple Sclermentioning
confidence: 99%
“…We infer that disruption of connectivity inside large-scale cortical networks, occurring as a consequence of diffuse white matter damage, may constitute the main neuronal mechanism of the deficit in controlled information processing in patients at the early stage of MS (Au Audoin et al, 2005;Deloire et al, 2005). Even if diffuse white matter injury may also alter or slow the conduction of information to primary visual and other specialized processing areas, one may expect encapsulated processes, supported primarily by short-and medium-range neuronal networks to have a greater probability of being preserved than higher level controlled processes, at least at the early stage of MS when no significant neuronal loss has been demonstrated Fernando et al, 2004;Ranjeva et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A first 1 H-MR spectroscopy study that included 20 patients with CIS demonstrated no significant metabolic alterations, whereas a second study from the same group that included 96 patients found a significant increase of mIns but no decrease of tNAA. 24,25 Although high-field MR imaging has been established in the clinical setting by now, most of the experiences in MR imaging and 1 H-MR spectroscopy on patients with CIS and MS are limited to field strengths up to 1.5T. 26 At greater magnetic fields, conventional MR imaging provides higher sensitivities in the detection of inflammatory brain lesions, and 1 H-MR spectroscopy is likely to be more sensitive in the quantification of brain metabolites because of increased signal intensity and improved spectral separation.…”
mentioning
confidence: 99%